HIV escape and attenuation by cytotoxic T lymphocytes. - Leslie, A; Goulder, P (2006)
PURPOSE OF REVIEW: Much of the current HIV-1 vaccine research focuses on harnessing the cytotoxic T-lymphocyte arm of the immune response. However, HIV-1 appears to have an unerring ability to evade cytotoxic T-lymphocyte responses, through the process of escape mutation, and thus the potential benefit of a cytotoxic T-lymphocyte-based vaccine remains uncertain. This review focuses on several recent studies that question whether escape mutation is always detrimental to the host, and may provide new hope for the success of a cytotoxic T-lymphocyte-based vaccine against HIV. RECENT FINDINGS: Several recent studies, in both natural HIV-1 infection and the SIV model, have identified examples of cytotoxic T-lymphocyte escape mutants that revert on transmission to individuals lacking the selecting major histocompatibility complex alleles. The obvious implication of these data is that some cytotoxic T-lymphocyte responses can only be evaded through escape mutations that actually reduce the replicative fitness of the virus. In addition, a recent vaccine study in macaques found that the control of immunodeficiency virus to undetectable levels was only achieved in animals that were able to force the virus to make such detrimental escape mutations. These data raise the intriguing possibility that, rather than undermining cytotoxic T-lymphocyte vaccines, escape mutation may be one of the keys to their success. SUMMARY: Clearly, not all escape mutations help to control viral replication. We discuss how these new data may assist in the struggle to develop a successful cytotoxic T-lymphocyte-based HIV vaccine, and what they tell us about the responses such a vaccine should aim to elicit.